EVALUASI IMPLEMENTASI PROGRAM PENERIMAAN SISWA BARU DI SMP NEGERI 50 PALEMBANG : id - Afif Alfiyanto Afif; Fitri Hidayati; Febriyanti; Farhani Aulia (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2022)
This study aims to determine the evaluation of the new student admissions program and the factors supporting and inhibiting the implementation of the new student admissions program at SMP Negeri 50 Palembang. This study uses a qualitative descriptive approach with field research methods (field research). Collecting data through interviews, observation, and documentation. The data were analyzed through several activities consisting of data reduction, data presentation procedures, and drawing conclusions. The results showed that the evaluation of the new student admission program at SMP Negeri 50 Palembang had been carried out well. Implementation of the new student admission program at SMP Negeri 50 Palembang through a system of zoning, transfer, parents, and achievement pathways. The series of procedures for new student admissions carried out by SMP Negeri 50 Palembang include; a) the formation of a committee; b) new student admissions meeting: c) making and posting announcements: d) registration: e) selection: f) announcements and re-announcements. Obstacles in implementing the new student admissions program are the use of social media that has not been maximized and the technologically backward problems that occur in a number of people in conducting online registration for new student admissions. The evaluation of the new student admission program at SMP Negeri 50 Palembang is quite good but it must still be considered and improved again so that it can run properly.